Single threshold optimization and a novel double threshold scheme for non‐line‐of‐sight identification. (13th November 2012) - Wu, Shixun; Li, Jiping; Liu, Shouyin
SUMMARY Non‐line‐of‐sight (NLOS) identification is a critical issue in wireless location system. The traditional method only considers the probability of false alarm to obtain the single threshold to identify the wireless propagation environment as line of sight (LOS) or NLOS. However, the probability of missed detection is rarely discussed. In this paper, firstly, the optimal single threshold is derived through minimizing the total error probability, which is the sum of the probability of false alarm and the probability of missed detection. Further, if the prior probabilities for the LOS and NLOS environment are available, a novel double threshold method based on the optimal single threshold is proposed to perform NLOS identification. By comparing the total error probability, we show through simulation results that the performance of the optimal single threshold is better than that of the traditional single threshold. Moreover, the novel double threshold NLOS identification scheme is feasible and better than the optimal single threshold scheme. It is also shown that the analytical results are consistent with the simulated ones.Copyright © 2012 John Wiley & Sons, Ltd.